Overexpression of Plasma Membrane H+-ATPase in Guard Cells Enhances Light-Induced Stomatal Opening, Photosynthesis, and Plant Growth in Hybrid Aspen - Toh, Shigeo; Takata, Naoki; Ando, Eigo; Toda, Yosuke; Wang, Yin; Hayashi, Yuki; Mitsuda, Nobutaka; Nagano, Soichiro; Taniguchi, Toru; Kinoshita, Toshinori (Frontiers in Plant Science, 2021)
Stomata in the plant epidermis open in response to light and regulate CO2 uptake for photosynthesis, and transpiration for uptake of water and nutrients from roots. Light-induced stomatal opening is mediated by activation of the plasma membrane (PM) H+-ATPase in guard cells. Overexpression of PM H+-ATPase in guard cells promotes light-induced stomatal opening, enhancing photosynthesis and growth in Arabidopsis thaliana. In this study, transgenic hybrid aspens overexpressing Arabidopsis PM H+-ATPase (AHA2) in guard cells under the strong guard cell promoter Arabidopsis GC1 (AtGC1) showed enhanced light-induced stomatal opening, photosynthesis, and growth. First, we confirmed that AtGC1 induces GUS expression specifically in guard cells in hybrid aspens. Thus, we produced AtGC1::AHA2 transgenic hybrid aspens and confirmed expression of AHA2 in AtGC1::AHA2 transgenic plants. In addition, AtGC1::AHA2 transgenic plants showed a higher PM H+-ATPase protein level in guard cells. Analysis using a gas-exchange system revealed that transpiration and the photosynthetic rate were significantly increased in AtGC1::AHA2 transgenic aspen plants. AtGC1::AHA2 transgenic plants showed a > 20% higher stem elongation rate than the wild type (WT). Therefore, overexpression of PM H+-ATPase in guard cells promotes the growth of perennial woody plants.